ANALISIS KEMAMPUAN LITERASI SAINS, SIKAP ILMIAH DAN MERANCANG MINI RISET MAHASISWA PGSD STKIP MUHAMMADIYAH BANGKA BELITUNG PADA MATA KULIAH PRAKTIKUM IPA - Erika Fitri Wardani (Primary Education Journal Silampari (PEJS), 2019)
This study aimed to 1) determined the scientific literacy skills of STKIP MBB PGSD students in Science Practicum Courses, 2) determined the ability of the scientific attitude of STKIP MBB PGSD students in Science Practicum Courses and 3) to knew the ability of STKIP MBB PGSD students in designing a mini research on Science Practicumcourse.This research was a qualitative descriptive method The study was conducted through descriptive analysis of variables measured in the study. The variables in question are scientific literacy skills, scientific attitudes and the ability to design mini research of STKIP Muhammadiyah Bangka Belitung PGSD students. Data collection techniques in this study include giving scientific literacy test questions, giving scientific attitude questionnaires, observing the ability of students to conduct mini research, interviews, and documentation. The research instruments used included scientific literacy questions, scientific attitude questionnaires, observation sheets of students' ability to conduct mini research, interview guides, and field notes.The results showed that science literacy skills of PGSD students were still in the low category with an average percentage of 49.64%, students' scientific attitudes were in a good category with an average percentage of 79.83% while the skills in designing mini research were in the sufficient category with a mean percentage amounting to 41.99%.